Genetic analysis reveals novel variants for vascular cognitive impairment - Mönkäre Saana; Kuuluvainen Liina; Schleutker Johanna; Bras Jose; Roine Susanna; Pöyhönen Minna; Guerreiro Rita; Myllykangas Liisa (WILEY, 2022)
Objectives
The genetic background of vascular cognitive impairment (VCI) is poorly understood compared to other dementia disorders. The aim of the study was to investigate the genetic background of VCI in a well-characterized Finnish cohort.
Materials & Methods
Whole-exome sequencing (WES) was applied in 45 Finnish VCI patients. Copy-number variant (CNV) analysis using a SNP array was performed in 80 VCI patients. This study also examined the prevalence of variants at the miR-29 binding site of COL4A1 in 73 Finnish VCI patients.
Results
In 40% (18/45) of the cases, WES detected possibly causative variants in genes associated with cerebral small vessel disease (CSVD) or other neurological or stroke-related disorders. These variants included HTRA1:c.847G>A p.(Gly283Arg), TREX1:c.1079A>G, p.(Tyr360Cys), COLGALT1:c.1411C>T, p.(Arg471Trp), PRNP: c.713C>T, p.(Pro238Leu), and MTHFR:c.1061G>C, p.(Gly354Ala). Additionally, screening of variants in the 3 ' UTR of COL4A1 gene in a sub-cohort of 73 VCI patients identified a novel variant c.*36T>A. CNV analysis showed that pathogenic CNVs are uncommon in VCI.
Conclusions
These data support pathogenic roles of variants in HTRA1, TREX1 and in the 3 ' UTR of COL4A1 in CSVD and VCI, and suggest that vascular pathogenic mechanisms are linked to neurodegeneration, expanding the understanding of the genetic background of VCI.